AN ANALYSIS OF LEXICAL SEMANTIC MEANING IN ALBUM “LOVER” BY TAYLOR SWIFT - Zulaikah Zulaikah; Nurul Hasanah; Dwi Astuti; Endang Komsatun (IKIP Siliwangi, 2024)
Language serves as a medium for communicating messages, whether through spoken or written means. An in-depth analysis of the meaning of words, phrases, and a sentences is crucial as it enhances the clarity of communication and allows for different perspectives on semantics. The term